Compare The Immunity Of An International Employee With Diplomatic Immunity - أحمد بسام; السيّد خلود (Latakia University Journal - Economic and Legal Sciences Series, 2021)
Diplomatic relations between countries went through many developments over different ages until they reached what they are now by diplomatic missions and envoys in other countries. The emergence of international organizations and their assumption of an important position in the international arena and their pursuit of goals by human cadres represented by international employees. The good performance of the diplomatic envoy and the international employee did not come from a vacuum. It is a combination of these people having high competence ، tact and the required educational qualifications. As well as granting these people the immunities and privileges، established in international and regional conventions، and recognized by the members of the whole international community، as a means of strengthening its relations at the international level. These immunities help them to fulfill the tasks assigned to them. The essence of these immunities is the interest of states and international organizations, not the personal interest of the diplomatic envoy or the international employee. Immunities for diplomatic envoys and international employees are graded according to the order of their job grades until some of them are absent.